Feline corneal sequestration - Oriá, Arianne Pontes [UNESP]; Soares, Ana Maria Barros [UNESP]; Laus, José Luiz [UNESP]; Dórea Neto, Francisco De Assis [UNESP] (Universidade Federal de Santa Maria, 2001)
Corneal sequestration is a disease unique to domestic cats, clinically characterized by chronicity; signs of ocular pain with the development of a dark brown to black, opaque, oval, paracentral or central corneal plaque. The purpose of this review article was to approach and discuss about the etiology, clinical manifestations, diagnosis, and treatment of the corneal sequestrum.

Seqüestro corneano é uma doença única dos gatos domésticos. Caracterizada clinicamente pela crônicidade, sinais de dor ocular, com desenvolvimento de placa marrom a enegrecida, opaca, de localização central ou paracentral. O propósito deste artigo de revisão é abordar e discutir questões sobre a etiologia, manifestações clínicas, diagnóstico e tratamento da enfermidade.
Seqüestração corneana dos felinos
Keywords: cats; corneal diseases; corneal sequestration; keratitis; ulcer; gatos; doenças corneanas; seqüestro corneano; ceratites; úlcera